HEROs: Design of a Mixed-Methods Formative Research Phase for an Ecocultural Intervention to Promote Healthy Eating and Activity Behaviors in Rural Families With Preschoolers - Bellows, Laura L. (J Nutr Educ Behav, 2018)
OBJECTIVE: To describe the mixed-methods formative research phase in the development of the Healthy Environments Study (HEROs), a technology-based, interactive family intervention to promote healthy eating and activity behaviors for young children in the home environment. DESIGN: A mixed-method iterative approach, using ecocultural theory as a framework, will guide the development of both quantitative and qualitative formative research assessments. SETTING: Rural eastern Colorado. PARTICIPANTS: Low-income families (n = 200) with preschool-aged children enrolled at 6 Head Start/preschool centers. MAIN OUTCOME MEASURES: Quantitative and qualitative methodologies will garner insights into 4 key topic areas: (1) food behaviors and environments (Remote Food Photography Method, parent focus group, and survey), (2) physical activity behaviors and environments (parent interview and survey), (3) mobile device use (parent survey and interview), and (4) daily life (ecocultural family interview and teacher/staff group discussions). ANALYSIS: Results will be interpreted in combination to allow for a holistic understanding of participant behaviors, beliefs, attitudes and values related to each of the 4 topic areas. Collectively, outcomes will provide a comprehensive picture of preschoolers’ daily life and inform intervention design and strategies to enhance preschoolers’ eating and activity behaviors in the home environment.